The Influence Of Safety Management Practices And Safety Self Efficacy On Safety Behaviour Among Assistant Medical Officer In Public Hospital - Thines, Ravy (2024)
Safety management practices and safety self-efficacy are critical factors influencing safety behavior among healthcare professionals, particularly Assistant Medical Officers (AMOs) in public hospitals. The aim of the study is to investigate the influence of safety management practices and safety self-efficacy on safety behavior among Assistant Medical Officers (AMOs) of Public Hospital, with the goal of identifying strategies to enhance safety outcomes and improve patient care quality. The study utilized a quantitative methodology, employing a cross-sectional explanatory design. The study focused on a population of 221 assistant medical officers within the hospital. A sample size of 141 participants was determined using the Raosoft Inc (2018). The questionnaire are administered in dual languages English and Bahasa Malaysia comprises 49 Questions. The management commitment dimension and safety and rules and procedure dimension found to have positive relationship towards safety behaviour while Safety training dimension, Employee involvement dimension, Safety communication dimension and Safety promotion dimension found to have no significant relationship to safety behaviour. Meanwhile, finding also shows that Safety self-efficacy is positively related to safety behaviour (safety compliance and safety participation). The findings of this study show significance of management commitment, adherence to safety rules and procedures, and safety self-efficacy in fostering safety-oriented behaviors among Assistant Medical Officers (AMOs) in hospital settings. Future study should focus on other hospitals that have higher number of workers. Besides that, the present study focused only on Assistant Medical Officers (AMOs). Future study should integrate other categories of hospital personnel to understand the differences among these groups in terms of their safety behaviour.